ANALYSIS OF STUDENT CREATIVE THINKING SKILLS IN SOLVING PROBLEM PATTERN NUMBERS WITH PARTITION TECHNIQUES BASED ON METACOGNITION SKILLS. - Nila Herawati, Dafik & I Made Tirta (International Journal of Research Science and Management, 2018)
High-order thinking or Higher Order Thinking Skill (HOTS) is one of the most needed thinking skills in a person's life. Creative thinking is the highest level of thinking skills. Creative thinking skills in students have the characteristics of fluency (fluency), flexibility (flexibility), elaboration and originality (originality). Metacognition is the ability of one's thinking in using strategies to produce problem solving in their learning. This ability helps students get personal feedback about their learning progress. From the research result, the students with high metacognition ability are at the level of creative thinking skill 4 (very creative), the student has been able to find the different pattern in the number pattern with the partition technique. Students with metacognition skills are at the creative skill level 3 (creative). While students with low metacognition abilities are at the level of creative thinking skills 2 (simply creative). Her creative thinking skill to 15 students can show his skill on fluency aspect, on flexibility aspect 11 students, while 5 students' originality aspect and elaboration aspects of 14 students. So the percentage of students with creative skill is on 100% fluency aspect, 73.3% flexibility aspect, 33,3% originality aspect and elaboration aspect 93,3%.